Bactericidal activity of nukacin ISK-1: an alternative mode of action. Issue 7 (3rd July 2014) - Roy, Urmi; Islam, Mohammad Riazul; Nagao, Jun-ichi; Iida, Hiroshi; Mahin, Abdullah-Al; Li, Mengqi; Zendo, Takeshi; Nakayama, Jiro; Sonomoto, Kenji
Abstract: We previously reported bacteriostatic action of nukacin ISK-1 against Bacillus subtilis JCM 1465 T . Here, we found its bactericidal activity against Micrococcus luteus DSM 1790 and Staphylococcus simulans 22, showing decrease in cell viability, cell lysis, and dissipation of the membrane potential. Moreover, leakage of small molecules such as K +, suggested the formation of small-sized or specific K + -conducting-pores by nukacin ISK-1.